Identification of a potent NAFLD drug candidate for controlling T2DM-mediated inflammation and secondary damage in vitro and in vivo - Samsuzzaman, Md; Lee, Jae Hyuk; Moon, Hyejin; Lee, Jisue; Lee, Heaji; Lim, Yunsook; Park, Myoung Gyu; Kim, Hakwon; Kim, Sun Yeou (Frontiers in Pharmacology, 2022)
Accumulation of glucose/sugar results in the formation of reactive di-carbonyl compounds like MGO and GO that interact with several amino acids and proteins to form toxic advanced glycation end products (AGEs). Induction of AGEs breakdown can control the symptoms and severity in T2DM and other related complications like NAFLD where AGEs are the key players. Therefore, an AGE cross-links breaker has been suggested for preventing the onset/progression of NAFLD. In this study, we reported novel synthetic naphthalene-2-acyl thiazolium derivatives (KHAGs). Among synthesized KHAG derivatives, we observed that a novel KHAG-04, a 1,4-dimethoxynaphthalen-2-acylthiazolium salt which is an analog of Alagebrium, dramatically cleaves MGO/GO-AGE cross-links, and it also inhibited inflammation by lowering the level of nitric oxide production, IL-1β and TNF-α secretion in LPS and/or MGO-AGEs activated macrophage. Moreover, it also reduced FFA and MGO-AGEs induced lipogenesis in Hep-G2 cells. In mice, KHAG-04 significantly reduced the level of glyoxal in the liver which was induced by DMC. Furthermore, KHAG-04 treatment significantly reduced the blood glucose levels, lipid accumulation, and inflammation in NAFLD/T2DM animal model. Novel KHAG-04-mediated induction of AGEs breakdown could be the possible reason for its anti-inflammatory, anti-hyperglycemic, and anti-lipidemic effects in cells and NAFLD in the T2DM animal model, respectively. Further research might explore the pharmacological efficacy, and usefulness and consider the ability of this compound in the treatment strategy against various models of NAFLD in T2DM where MGO/GO-AGEs play a key role in the pathogenesis.